MASONRY AND MODERN TIMES: REBIRTH OF THE MOVEMENT IN ARMENIA (ANALYSIS OF REPUBLICAN PRESS) - M. Avagyan (International Journal of Innovative Technologies in Social Science, 2022)
The paper is dedicated to the topic of Masonry given day-to-day realities. The publications in the Armenian periodicals related to the rebirth of Masonry movements on post-Soviet territory, in particular in Armenia, are analyzed. The study draws parallels between century-long Masonry and newly made Masonic lodges. Historical realities, as a rule, condition today’s perception of Masonic movement in Armenia which is why very often this phenomenon is interpreted ambiguously, at times being covered in a veil of mystery or, even worse, negativity. There is every indication of unreliability and lack of verification of information, various defamations and hypotheses which confuse the uneducated minds resulting in quite a natural misunderstanding.